2017
DOI: 10.5194/tc-11-841-2017
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of two alpine rock glaciers investigated by quasi-3-D electrical resistivity imaging

Abstract: Abstract. Interactions between different formative processes are reflected in the internal structure of rock glaciers. Therefore, the detection of subsurface conditions can help to enhance our understanding of landform development. For an assessment of subsurface conditions, we present an analysis of the spatial variability of active layer thickness, ground ice content and frost table topography for two different rock glaciers in the Eastern Swiss Alps by means of quasi-3-D electrical resistivity imaging (ERI)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Lower frequency GPR will allow measurement to greater depths but with the drawback of less detailed information. Geoelectric investigations are especially suitable for higher resolution results including detecting ground ice (Ribolini et al, ; Emmert and Kneisel, ) although the depth of application is quite limited and they require intensive and laborious fieldwork, and are therefore more suitable for smaller landforms.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Lower frequency GPR will allow measurement to greater depths but with the drawback of less detailed information. Geoelectric investigations are especially suitable for higher resolution results including detecting ground ice (Ribolini et al, ; Emmert and Kneisel, ) although the depth of application is quite limited and they require intensive and laborious fieldwork, and are therefore more suitable for smaller landforms.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…1b) to image the internal structure (Hauck and Kneisel, 2008;Kneisel et al, 2008) and to quantify its material composition based on a petrophysical model, the so-called Four-Phase Model (4PM, see below) (Hauck et al, 2011). Previous studies on the internal structure of rock glaciers have revealed large spatial heterogeneities in material composition within single landforms (Emmert and Kneisel, 2017;Hausmann et al, 2012;Monnier and Kinnard, 2013;Springman et al, 2012). 210…”
Section: Geophysicsmentioning
confidence: 99%
“…New approaches include the possible estimation of ground ice variation through subsidence measurements using reflected GNSS signals (Liu and Larson, 2018) or through spaceborne gravity measurements (e.g., Vey et al, 2012). Since information from one method is often ambiguous, many cryogeophysical studies use a combination of different geophysical methods (e.g., Hausmann et al, 2007;Kneisel et al, 2008;Doetsch et al, 2012;Buchli et al, 2013;Parsekian et al, 2015;Briggs et al, 2016;Merz et al, 2016;Pellet et al, 2016;Emmert and Kneisel, 2017;LĆ©ger et al, 2017;Mewes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%